2018
DOI: 10.18502/avr.v27i4.127
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the quick speech-in-noise test results in migraineurs without aura and normal subjects

Abstract: Background and Aim: Migraine is a relatively common neurovascular disease. Audiology studies have shown some ways of influencing migraine by the auditory pathways from cochlea to the auditory cortex. Considering that one of the most important functions of the central auditory system is speech perception in challenging conditions, the purpose of this study was to evaluate the ability to understand speech in noise in migraineurs without aura, and compare it with normal subjects.Methods: In this cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…This finding proved that migraine patient had severely impaired speech discrimination in noise, with no difference between the two study groups (Table 9). This agreed with Hosein et al [32] who reported that migraine patients without aura have difficulty in speech perception in background noise, and their signal noise ratio [SNR] loss in quick speech in noise [Q-SIN] test The most common complaint for both groups was problems in memory and attention (especially in the VM group), followed by difficulty in understanding speech in background noise (75% of the VM group and 65% of the migraine group). Also, about half of both groups complained of previous problems in education mostly were memory and concentration problems showed an abnormal increase compared to the group.…”
Section: Inclusion Criteriasupporting
confidence: 89%
See 1 more Smart Citation
“…This finding proved that migraine patient had severely impaired speech discrimination in noise, with no difference between the two study groups (Table 9). This agreed with Hosein et al [32] who reported that migraine patients without aura have difficulty in speech perception in background noise, and their signal noise ratio [SNR] loss in quick speech in noise [Q-SIN] test The most common complaint for both groups was problems in memory and attention (especially in the VM group), followed by difficulty in understanding speech in background noise (75% of the VM group and 65% of the migraine group). Also, about half of both groups complained of previous problems in education mostly were memory and concentration problems showed an abnormal increase compared to the group.…”
Section: Inclusion Criteriasupporting
confidence: 89%
“…The correlation studies that compared the duration of migraine, the frequency of attack, and the central auditory test results in study group I showed that there was no correlation (Tables 12 and 13). Similarly, Hosein et al [32] found that migraine patients without aura have difficulty in speech perception in background noise, but there was no correlation between the duration of the disease or the frequency of attacks and [SNR] loss. Also, Bockowski et al [38] on their study on cortical event-related potentials [CERP] in children with migraine headache found that no significant correlation between [CERP] parameters and duration of disease.…”
Section: Inclusion Criteriamentioning
confidence: 99%